Pathoproteomics of testicular tissue deficient in the GARP component VPS54: The wobbler mouse model of globozoospermia. Issue 7 (13th November 2013) - Jockusch, Harald; Holland, Ashling; Staunton, Lisa; Schmitt‐John, Thomas; Heimann, Peter; Dowling, Paul; Ohlendieck, Kay; Lodeiro, Carlos; Martínez, José Luis Capelo; Santos, Hugo M.
<x xml:space="preserve">Abstract</x> In human globozoospermia, round‐headed spermatozoa lack an acrosome and therefore cannot properly interact with oocytes. In the wobbler (WR) mouse, an L967Q missense mutation in the vesicular protein‐sorting factor VPS54 causes motor neuron degeneration and globozoospermia. Although electron microscopy of WR testis shows all major components of spermatogenesis, they appear in a deranged morphology that prevents the formation of the acrosome. In order to determine proteome‐wide changes, affected testes were analysed by 2D‐DIGE and MS. The concentration of 8 proteins was increased and that of 35 proteins decreased as compared to wild type. Mass spectrometric analysis identified proteins with an altered concentration to be associated with metabolite transport, fatty acid metabolism, cellular interactions, microtubule assembly and stress response (chaperones Hsp70–2 and Hsp90α). Minor changes were observed for proteins involved in cell redox homeostasis, cytoskeleton formation, PTMs, detoxification and metabolism. The most dramatically decreased protein in WR testis was identified as fatty acid binding protein FABP3, as confirmed by immunoblot analysis. We conclude that a missense mutation in VPS54, an essential component of the Golgi‐associated retrograde protein complex, not only prevents the formation of an acrosome but also initiates a cascade of metabolic abnormalities and a stress reaction.